What it feels like to be a building - Wilson, Forrest, 1918- (Washington, DC : Preservation Press, 1988)
Explains how different parts of a building, such as columns, walls, beams, buttresses, rods, and cables, function to support great weight and stress.
School Library Journal.
Booklist.
5.5
5-8
Keywords: Structural engineering -- Juvenile literature; Buildings -- Juvenile literature; Structural engineering; Buildings; Structural engineering; Buildings; Structural engineering; Buildings